A chloroplast genome of Forsythia saxatilis (Nakai) Nakai, an endemic species in Korea. Issue 3 (2nd July 2020) - Choi, Sang Chul; Kim, Sangtae
Abstract: Forsythia saxatilis (Nakai) Nakai is an endemic species in Korea. We present the second complete chloroplast genome sequence of F. saxatilis showing that the chloroplast genome is 156, 376 bp in length containing four subregions: a large single-copy (LSC) region of 87, 097 bp, a small single-copy (SSC) region of 17, 859 bp, and a pair of inverted repeat regions (IRs) of 25, 710 bp. The genome contains 131 genes including 88 protein-coding genes, 35 tRNA s, and eight rRNAs. We found 40 base differences in 17 sites between our chloroplast genome and the previously reported chloroplast genome sequences of F. saxatilis . All of the differences were found in a region of 832 bp in the LSC region except for one site, which indicated potential sequencing errors in building the previously reported genome because of little substitutions in the homologous region of the other Forsythia species and even of Abeliophyllum distichum, a sister to Forsythia . The new chloroplast genomes of F. saxatilis and those of F. x intermedia and F. viridissima are identical, which suggests that F. saxatilis is maternally closely related to the other two species.